Growth and morphogenesis of an autonomic ganglion. II. Establishment of neuron position - Heathcote, RD (J Neurosci, 1987)
The developmental events affecting the positioning of neurons were examined in the frog cardiac ganglion. Use of a neuron-specific marker enabled the position of all neurons in the ganglion to be quantified at different developmental stages. Subsets of neurons born at specific times were labeled with 3H-thymidine, and their positions were mapped at different developmental stages. This technique identifies a subset of cells within a seemingly homogeneous pool of neurons and provides an opportunity for studying the position of individual neurons during ganglion morphogenesis. Comparison of identified neurons in different animals has revealed several unexpected results. First, during a period of dramatic ganglion and cellular morphogenesis there is little or no cell death since the number of identified neurons does not change during this time. Second, the distinctive clusters that are characteristic of parasympathetic ganglia have been shown to be ephemeral because identified cells that were neighbors early in development become separated during ganglion morphogenesis. Third, individual postmitotic neurons do not actively migrate to produce the observed changes in neuron distribution, as evidenced by the fact that their relative position in the ganglion is maintained. Fourth, both ganglion and target undergo intercalary growth since the absolute distance of identified neurons from one another increases while the relative distance remains the same. Finally, the differentiation of neurons is analogous to the inside-out pattern seen in many parts of the CNS. Thus the ability to identify cells within a large ensemble of seemingly equivalent neurons has made it possible to investigate ganglion morphogenesis at the level of individual cells.